Learning by creating: "Creative Factory" in university classroom. - Israel Alonso Saez; Maite Arandia Loroño (Universitat Politècnica de València, 2014)
The methodological innovation experience "Creative Factory" presented in this article was developed during the course 2011/2012 and 2012/2013 in the subject of General Didactics in the Degree in Social Education at the University of the Basque Country (UPV/EHU). The main purpose that has been pursued has been to provide students a formative context and learning opportunities to live and analyze the creative methodology of Creative Factory when performing a diagnosis of needs, to generate innovative ideas and to design intervention socioeducational projects. Also, to encourage in students a motivating, meaningful, functional and creative learning. The experience has been developed within seminars in which the large group is divided into groups of about fifteen people to perform tasks of deepening or enriching of the theory classes. This kind of grouping makes sure that students have more possibilities of a communicative interaction and favors a relaxed and open participation. In this article we report the theoretical foundation, the methodological procedure followed as well as its theoretical foundation in the socio educative world from which we have incorporated the results obtained from the evaluation process conducted with the students during the work process, the most important conclusions to which we have arrived and the lines of improvement to be introduced in the coming years.